summaryrefslogtreecommitdiff
path: root/Assignment1
diff options
context:
space:
mode:
Diffstat (limited to 'Assignment1')
-rw-r--r--Assignment1/conversion.tex111
1 files changed, 102 insertions, 9 deletions
diff --git a/Assignment1/conversion.tex b/Assignment1/conversion.tex
index 7635f05..607d030 100644
--- a/Assignment1/conversion.tex
+++ b/Assignment1/conversion.tex
@@ -91,6 +91,7 @@ For the proofs of the equivalences, we refer the reader to the appendix of \cite
\erin
\begin{enumerate}[resume]
\item Suppose $E = q \Sop (a \wedge \neg (\alpha \Uop \beta))$, then $E \equiv E_1 \vee E_2 \vee E_3$ where:
+ % TODO Verify all except 3
\begin{align*}
E_1 &= (a \wedge \neg \beta \Sop a) \wedge \neg \beta \wedge \neg (\alpha \Uop \beta)\\
E_2 &= \neg \beta \wedge \neg \alpha \wedge (\neg \beta \wedge q \Sop a)\\
@@ -99,9 +100,9 @@ For the proofs of the equivalences, we refer the reader to the appendix of \cite
\item Suppose $E = q \Sop (a \wedge \neg (\alpha \Uop \beta))$, then $E \equiv E_1 \vee E_2 \vee E_3$ where:
\begin{align*}
- E_1 &= (q \wedge \neg \beta \Sop a) \wedge \neg \beta \wedge \neg (\alpha \Uop \beta)\\
- E_2 &= \neg \beta \wedge \neg \alpha \wedge (\neg \beta \wedge q \Sop a)\\
- E_3 &= q \Sop (\neg \beta \wedge \neg \alpha \wedge q \wedge (\neg \beta \wedge q \Sop a))
+ E_1 &= (q \wedge \neg \beta) \Sop a \wedge \neg \beta \wedge \neg (\alpha \Uop \beta)\\
+ E_2 &= \neg \alpha \wedge \neg \beta \wedge (\neg \beta \wedge q) \Sop a\\
+ E_3 &= q \Sop (\neg \alpha \wedge \neg \beta \wedge q \wedge (\neg \beta \wedge q) \Sop a)
\end{align*}
\item Suppose $E = (q \vee \neg (\alpha \Uop \beta)) \Sop a$, then $E \equiv \neg (\neg a \Sop \neg q \wedge (\alpha \Uop \beta) \wedge \neg a) \wedge \Fop^{-1} a$,
@@ -145,7 +146,7 @@ The final step of the algorithm entails removing the parts of the formula that c
\camil
\begin{example}[Properties for an Authentication System]
Consider again the property from \cref{ex:pltl:authentication-system}, repeated here with less verbose names:
- $\square (c \rightarrow \lnot f \Sop s)$.
+ $\phi = \square (c \rightarrow \lnot f \Sop s)$.
This can be rewritten to a form with only $\Uop$ and $\Sop$:
\begin{align*}
\square(c \rightarrow \lnot f \Sop s)
@@ -157,12 +158,104 @@ The final step of the algorithm entails removing the parts of the formula that c
\begin{align*}
\lnot (\top \Uop (c \land \lnot(\lnot f \Sop s)))
&\rightarrow \lnot (\top \Uop (c \land \lnot(s \lor \lnot f \land \lnot f \Sop s)))\\
- &\equiv \lnot (\top \Uop (c \land \lnot s \land f \land \lnot (\lnot f \Sop s))) \\
- &\rightarrow \lnot ((c \land \lnot s \land f \land \lnot (\lnot f \Sop s)) \lor (\top \Uop (c \land \lnot s \land f \land \lnot (\lnot f \Sop s))))\\
- &\equiv \lnot (c \land \lnot s \land f \land \lnot (\lnot f \Sop s)) \land \lnot(\top \Uop (c \land \lnot s \land f \land \lnot (\lnot f \Sop s)))\\
- &\equiv (\lnot c \lor s \lor \lnot f \Sop s) \land \lnot(\top \Uop (c \land \lnot s \land f \land \lnot (\lnot f \Sop s))).
+ &\equiv \lnot (\top \Uop (c \land \lnot s \land (f \lor \lnot (\lnot f \Sop s)))) \\
+ &\equiv \lnot (\top \Uop (c \land \lnot s \land f) \lor \top \Uop (c \land \lnot s \land \lnot (\lnot f \Sop s))) \\
+ &\rightarrow \lnot \big(
+ [c \land \lnot s \land f]
+ \lor [\top \Uop (c \land \lnot s \land f)]
+ \\&\quad\qquad\lor [c \land \lnot s \land \lnot (\lnot f \Sop s)]
+ \lor [\top \Uop (c \land \lnot s \land \lnot (\lnot f \Sop s))]\big)\\
+ &\equiv \lnot \big(
+ [c \land \lnot s \land (f \lor \lnot (\lnot \Sop s))]
+ \lor [\top \Uop (c \land \lnot s \land f)]
+ \\&\quad\qquad\lor [\top \Uop (c \land \lnot s \land \lnot (\lnot f \Sop s))]\big)\\
+ &\equiv
+ \lnot [c \land \lnot s \land (f \lor \lnot (\lnot f \Sop s))]
+ \land \lnot [\top \Uop (c \land \lnot s \land f)]
+ \\&\quad\qquad\land \lnot [\top \Uop (c \land \lnot s \land \lnot (\lnot f \Sop s))]\\
+ &\equiv
+ [\lnot c \lor s \lor (\lnot f \land \lnot f \Sop s)]
+ \land \lnot [\top \Uop (c \land \lnot s \land f)]
+ \\&\quad\qquad\land \lnot [\top \Uop (c \land \lnot s \land \lnot (\lnot f \Sop s))]\\
+ \end{align*}
+ Only the subterm $\top \Uop (c \land \lnot s \land \lnot (\lnot f \Sop s))$ needs to be rewritten in step 2.
+ Rule 3 applies (with $\Sop$ and $\Uop$ swapped).
+ This gives:
+ \begin{align*}
+ \top \Uop (c \land \lnot s \land \lnot (\lnot f \Sop s))
+ &\equiv
+ \lnot s \Uop (c \land \lnot s) \land \lnot s \land \lnot (\lnot f \Sop s)
+ \\&\qquad \lor f \land \lnot s \land \lnot s \Uop (c \land \lnot s)
+ \\&\qquad \lor \top \Uop (f \land \lnot s \land \lnot s \Uop (c \land \lnot s))
+ \end{align*}
+ And hence our original formula is initially equivalent to:
+ \begin{alignat*}{3}
+ \phi \equiv_0\enspace
+ & &&[\lnot c \lor s \lor (\lnot f \land \lnot f \Sop s)]
+ \land \lnot [\top \Uop (c \land \lnot s \land f)]\\
+ & &&\quad\land \lnot
+ \big[
+ \lnot s \Uop (c \land \lnot s) \land \lnot s \land \lnot (\lnot f \Sop s)
+ \\& &&\qquad\qquad \lor f \land \lnot s \land \lnot s \Uop (c \land \lnot s)
+ \\& &&\qquad\qquad \lor \top \Uop (f \land \lnot s \land \lnot s \Uop (c \land \lnot s))
+ \big]
+ \end{alignat*}
+ In step 3, we remove the pure past formulas from the boolean combination:
+ \begin{alignat*}{3}
+ \phi \equiv_0\enspace
+ & &&[\lnot c \lor s \lor \lnot f]
+ \land \lnot [\top \Uop (c \land \lnot s \land f)]
+ \\& &&\quad\land \lnot [\lnot s \Uop (c \land \lnot s) \land \lnot s]
+ \\& &&\quad\land \lnot [f \land \lnot s \land \lnot s \Uop (c \land \lnot s)]
+ \\& &&\quad\land \lnot [\top \Uop (f \land \lnot s \land \lnot s \Uop (c \land \lnot s))]\\
+ \equiv_0\enspace
+ & &&[\lnot c \lor s \lor \lnot f]
+ \land \lnot [\top \Uop (c \land \lnot s \land f)]
+ \\& &&\quad\land [\lnot (\lnot s \Uop (c \land \lnot s)) \lor s]
+ \\& &&\quad\land [\lnot f \lor s \lor \lnot (\lnot s \Uop (c \land \lnot s))]
+ \\& &&\quad\land \lnot [\top \Uop (f \land \lnot s \land \lnot s \Uop (c \land \lnot s))]
+ \end{alignat*}
+ We can rewrite this back to our semantics of $\Uop$:%
+ \footnote{The first two terms (the first line of the original formula) are collapsed into one term.
+ This is because Gabbay's $\phi \land \lnot(\top \Uop \lnot\phi)$ is equivalent to our $\lnot (\top \Uop \lnot\phi)$ (and hence $\square\phi$).
+ The same can be done for the last two terms (the last two lines of the original formula).
+ The third term can be rewritten via $\Xop$:
+ $\lnot (\lnot \phi \Uop \psi) \lor \phi
+ \enspace\rightarrow\enspace \psi \lor \lnot\Xop (\lnot\psi \Uop \phi)
+ \enspace\equiv\enspace \lnot(\lnot \psi \land \Xop (\lnot \psi \Uop \phi))
+ \enspace\equiv\enspace \lnot(\lnot\psi \Uop \phi)$.}
+ \begin{align*}
+ \dots &\rightarrow\enspace
+ \lnot [\top \Uop (c \land \lnot s \land f)]
+ \enspace\land\enspace \lnot (\lnot s \Uop (c \land \lnot s))
+ \enspace\land\enspace \lnot [\top \Uop (f \land \lnot s \Uop (c \land \lnot s))]\\
+ &\equiv\enspace
+ \square\lnot(c \land \lnot s \land f)
+ \enspace\land\enspace \lnot (\lnot s \Uop (c \land \lnot s))
+ \enspace\land\enspace \square\lnot(f \land \lnot s \Uop (c \land \lnot s))\\
+ &\equiv\enspace
+ \square\lnot(c \land \lnot s \land f)
+ \enspace\land\enspace \lnot \psi
+ \enspace\land\enspace \square\lnot(f \land \psi)
+ \quad \text{where $\psi = \lnot s \Uop (c \land \lnot s)$}\\
+ &\equiv\footnotemark\enspace
+ \lnot \psi
+ \enspace\land\enspace \square\lnot(f \land \psi)
\end{align*}
- % TODO: step 2 and 3 on the right part (S nested in U)
+ \footnotetext{Because $\square\lnot(f \land \psi) \equiv \square\lnot(c \land \lnot s \land f)$.}
+ Consider again the semantics of $c$, $s$ and $f$:
+ if $c$, a connection is established.
+ $s$ indicates that authentication succeeded; $f$ that authentication failed.
+ Thus, $\psi$ means that a connection will be established without authentication success.
+ The two terms of the conjunction then mean:
+ \begin{itemize}
+ \item $\lnot\psi$.
+ A connection cannot be established without prior authentication success.
+ \item $\square\lnot(f \land \psi)$.
+ After an authentication failure, a connection cannot be established without prior authentication success.
+ \end{itemize}
+ We see that the formula is reasonably succinct compared to its PLTL version, $\square(c \rightarrow \lnot f \Sop s)$.
+ Using past modalities was not needed in this case.
\end{example}
\erin